Digital Preservation of Qur’anic Manuscript: Developing the Manuscript Al-Qur’an Digital Application (MAQDA) - Aini, Adrika Fithrotul; Prajawinanti, Arin; Sulton, Agus; Alifa, Alifia Zuhriatul (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This article addresses the critical need for the preservation of Qur’anic manuscripts, focusing on the role of media transfer or digitization in safeguarding these valuable artifacts. The paper explores two main questions: the most effective preservation methods for ancient manuscripts and the contribution of mobile-based applications in disseminating information about these heritage objects. A qualitative research approach, combining philological and facsimile methods, was employed. The research focused on Qur’anic manuscripts held by individual collectors and pesantrens in the East Java region. Data were analyzed using the Miles and Huberman technique, involving stages of data arrangement, organization, and categorization. The findings revealed that mobile-based applications offer an efficient and cost-effective solution for preserving Qur’anic manuscripts, which are in deteriorating conditions. More than ten manuscripts observed in this study face inadequate storage and maintenance conditions. The development of the MAQDA digital application is a strategic and practical step for preserving these manuscripts. The study also emphasizes the need to make privately held manuscripts publicly accessible, raising awareness about the importance of preserving tangible cultural heritage. This paper contributes to the field of manuscript conservation, preservation, and digitization, highlighting the urgent need to safeguard numerous manuscripts, other than Qur’anic texts that are at risk and remain in private hands without infringing on ownership rights.